Sustainable thermal technologies and care homes: Productive alignment or risky investment?. (September 2015) - Neven, Louis; Walker, Gordon; Brown, Sam
Abstract: The use of more sustainable thermal technologies is a policy imperative across the UK building stock. However, not all building uses provide the same opportunities for technology uptake as others. Care homes for older people have characteristics which in technical and economic terms suggest that they might be particularly appropriate for the implementation of more sustainable thermal technologies. They have comparatively high demands for space heating and hot water often sustained on a 24/7 basis. However there are many considerations, both generic and contextual, that will typically play into processes of technology uptake. Through qualitative research in six case study homes, focused on management and staff perspectives and experiences, we explore the degree to which there might be a productive alignment between care home operation and the use of sustainable thermal technologies. Two key themes emerge focused on business considerations and the importance of avoiding risk and damage to reputation; and the ways in which different thermal technologies are relevant to and can potentially impact on care practices. We conclude that despite potential benefits the sector could remain rather resistant to sustainability innovations. We suggest therefore areas in which productive action and further research could be undertaken. Highlights: Care homes for older people might be particularly appropriate for the use of sustainable thermal technologies. We examine if a productive alignment between care homes and the use of sustainable thermal technologies does exist in practice. Two key themes are risks to business reputation; and relevance and potential benefits to care practices. We conclude that the sector could remain rather reluctant to embrace sustainability innovation.